Development Of Picture Story Books As A Media For Increasing Students' Creativity Based On Character Education - Zuhdi, A; Rasmuin, Rasmuin; Marandy, Yuniar Setyo (ZAHRA: Research and Tought Elementary School of Islam Journal, 2024)
Students are creative individuals. They have characteristics that are created to be classified as characteristics of creative individuals. For example, there is a great curiosity in terms of understanding, always asking questions, having high imagination, lots of interests, not being afraid of making mistakes, being brave in facing risks, being free when thinking, being happy about new things, and so on. The implementation of character education carried out at Madrasah Ibtidaiyyah Al Hidayah Sumenep Madura is still being implemented into daily habituation activities at school, but there has been no effort to develop story books that tell stories reflecting character education which emphasizes cultivating 18 characters in children. Research and development uses a model adapted by Borg and Gall. Of the ten development steps, researchers only implemented seven development steps. The results of this development show 1) the module specifications consist of a cover, introductory remarks, table of contents, materials, evaluation questions, and author biodata. The results of the research were 90.6% content experts with good qualifications, 89.3% learning media experts with good qualifications, and 94.6% learning experts with good qualifications. 2) The results of the attractiveness of the module, the researcher conducted a post-test in class on 10 students with an achievement percentage of 91.8% with very good qualifications. This shows that the use of picture storybooks has reached the criteria of being interesting and valid. Data analysis used the Paired Samples T Test with SPSS 16 tools and the results were Sig 0.000 < 0.02, so Ho was rejected, meaning that there were differences in learning outcomes from students who had used picture story books. So it can be concluded that the use of picture storybooks can increase creativity and is based on character education.